Genotypic capacity of post-anthesis stem reserve mobilization in wheat for yield sustainability under drought and heat stress in the subtropical region - Gurumurthy, S.; Arora, A.; Krishna, Hari; Chinnusamy, V.; Hazra, K. K. (Frontiers in Genetics, 2023)
Wheat productivity is severely affected by drought and heat stress conditions worldwide. Currently, stem reserve mobilization (SRM) is receiving increased attention as a trait that can sustain wheat yields in adverse environments. However, the significance of SRM in sustaining wheat yields under drought and heat stress conditions remains uncertain in tropical climate of Indo-Gangetic plain region. Therefore, this study aimed to investigate genotypic variations in SRM in wheat and their influence on yield sustainability under drought and heat stress environments. The experiment was designed in an alpha-lattice layout, accommodating 43 genotypes under four simulated environments [timely-sown and well-irrigated (non-stress); timely-sown and water-deficit/drought stress; late-sown and well-irrigated crop facing terminal high temperature; and late-sown and water-deficit stress (both water-deficit and heat stress)]. The water-deficit stress significantly increased SRM (16-68%, p < 0.01) compared to the non-stress environment, while the heat-stress conditions reduced SRM (12-18%). Both SRM and stem-reserve mobilization efficiency (SRE) exhibited positive correlations with grain weight (grain weight spike-1) under all three different stress treatments (p < 0.05). Strong positive correlations between stem weight (at 12 days after anthesis) and grain weight were observed across the environments (p < 0.001), however, a significant positive correlation between stem weight and SRM was observed only with the stress treatments. Results revealed that SRM trait could effectively alleviate the impacts of water-deficit stress on yield. However, the SRM-mediated yield protection was uncertain under heat-stress and combined water-deficit and heat-stress treatments, possibly due to sink inefficiencies caused by high-temperature during reproductive period. Defoliated plants exhibited higher SRM than non-defoliated plants, with the highest increment observed in the non-stress treatment compared to all the stress treatments. Results revealed that wider genetic variability exists for the trait SRM, which could be used to improve wheat yield under drought stress conditions.